Imidazole functionalized inorganic nanoparticle hybrid gel electrolyte, preparation method and application thereof

CN123033899APending Publication Date: 2026-11-03FUDAN UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611212081.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

现有纤维染料敏化太阳能电池在高温条件下存在电解液与染料分子反应导致的性能衰减、凝胶体系结构松弛及离子传输失控问题,影响器件在极端环境中的应用。

Method used

An imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte is used. By forming a complex with free iodine molecules through imidazole groups and combining inorganic nanoparticles as structural nodes, an organic-inorganic hybrid gel network is constructed to improve the thermal stability and ion conductivity of the battery.

Benefits of technology

It significantly improves the high-temperature stability and flexibility of fiber dye-sensitized solar cells while maintaining photoelectric conversion performance, making them suitable for harsh scenarios such as wearable devices and outdoor equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123033899A_ABST
    Figure CN123033899A_ABST
Patent Text Reader

Abstract

The application discloses an imidazole functionalized inorganic nanoparticle hybrid gel electrolyte as well as a preparation method and application thereof, and belongs to the technical field of photovoltaics. The gel electrolyte forms an organic-inorganic hybrid gel network by using a polyurethane polymer containing imidazole functionalized inorganic nanoparticles, and accommodates an electrolyte containing an iodine redox couple to form a hybrid gel electrolyte. The imidazole functionalized inorganic nanoparticles are obtained by reacting inorganic nanoparticles with an imidazole-containing silane precursor. The polyurethane polymer is formed by in-situ polymerization of a monomer containing an isocyanate group and a monomer containing a hydroxyl group. The fiber gel dye-sensitized solar cell prepared by the application has significantly improved high-temperature stability, excellent flexibility and good photoelectric conversion performance, and is suitable for flexible photovoltaic device applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photovoltaic technology, and particularly relates to an imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte, its preparation method, and its application. Background Technology

[0002] With the increasing popularity of wearable electronic devices, smart textiles, human-computer interaction systems, and health monitoring devices, flexible self-powered energy devices have become a research hotspot in this field. Fiber dye-sensitized solar cells (FDSSCs) have shown broad application prospects in the field of flexible photovoltaics due to their good flexibility, weavability, and low manufacturing cost.

[0003] Currently, fiber dye-sensitized solar cells commonly employ liquid electrolyte systems. However, liquid electrolytes have inherent drawbacks such as volatility and leakage, which can lead to device performance degradation and even safety issues under prolonged bending, twisting, or complex environmental conditions. Therefore, those skilled in the art have proposed replacing liquid electrolytes with gel electrolytes, utilizing polymer networks to physically confine the electrolyte, thereby improving the safety and stability of the device.

[0004] However, existing gel electrolytes still have significant shortcomings under high-temperature conditions. Specifically, when the operating temperature exceeds 60°C, free iodine molecules in the electrolyte readily undergo coordination substitution reactions with the -NCS groups in dye molecules such as N719. This leads to changes in the energy level structure of the dye molecules, a decrease in light absorption performance, and intensified electron recombination, ultimately resulting in irreversible degradation of the device's photoelectric conversion performance. Simultaneously, high-temperature conditions also cause relaxation of the internal structure of the gel system, uncontrolled ion transport, and deterioration of mechanical properties, severely limiting the practical application of such devices in extreme high-temperature scenarios such as desert environments, outdoor equipment, automotive exteriors, and spacesuits.

[0005] In summary, there is an urgent need in this field to develop an electrolyte system for fiber gel dye-sensitized solar cells that combines excellent high-temperature stability, high ion conductivity, and good flexibility, in order to promote the practical application of flexible photovoltaic devices. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention proposes an imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte, its preparation method, and its application. This electrolyte can significantly improve the thermal stability of fiber dye-sensitized solar cells.

[0007] To achieve the above objectives, the present invention provides the following technical solution: An imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte is formed by using a polyurethane polymer containing imidazole-functionalized inorganic nanoparticles to form an organic-inorganic hybrid gel network, and accommodating an electrolyte containing an iodine redox couple to form a hybrid gel electrolyte. The imidazole-functionalized inorganic nanoparticles are obtained by reacting inorganic nanoparticles with an imidazole-containing silane precursor. The polyurethane polymer is formed by in-situ polymerization of monomers containing isocyanate groups and monomers containing hydroxyl groups.

[0008] This invention introduces imidazole-functionalized inorganic nanoparticles. Due to the imidazole groups modified on their surface, these nanoparticles can act as Lewis base sites, forming complexes with free iodine molecules in the electrolyte. This regulates the disordered and violent movement of iodine at high temperatures, thereby suppressing the destructive effect of iodine on dye molecules under high-temperature conditions and effectively improving the thermal stability of the battery. Furthermore, as structural nodes in the gel network, the inorganic nanoparticles can reduce the local crystallinity of the polymer, increase the proportion of amorphous regions in the gel system, and thus improve the ionic conductivity and mechanical stability of the gel electrolyte.

[0009] Furthermore, the inorganic nanoparticles are metal oxide nanoparticles with hydroxyl groups on their surface, selected from one or more of aluminum oxide (Al2O3), silicon dioxide (SiO2), titanium dioxide (TiO2), zinc oxide (ZnO), zirconium oxide (ZrO2), and iron oxide (Fe2O3 or Fe3O4); the average particle size of the inorganic nanoparticles is 5-200 nm.

[0010] This invention utilizes metal oxide nanoparticles with hydroxyl-rich surfaces to ensure efficient chemical coupling reactions with imidazole silane precursors, forming a stable covalently modified layer. Simultaneously, controlling the particle size within the 5–200 nm range ensures that the nanoparticles have a sufficiently high specific surface area to provide abundant reaction sites and complexing active centers, while avoiding excessive particle aggregation. This facilitates the formation of a uniformly dispersed reinforcing phase within the gel network, further optimizing the mechanical properties and ion conductivity uniformity of the gel electrolyte.

[0011] Furthermore, in the preparation process of the imidazole-functionalized inorganic nanoparticles, the imidazole-containing silane precursor is obtained by reacting an amine compound containing a complex nitrogen heterocycle with an isocyanate-containing siloxane in an organic solvent.

[0012] This invention specifies the preparation of an imidazole-containing silane precursor via the reaction of an amine compound containing a complex nitrogen heterocycle with an isocyanate-containing siloxane. This route utilizes the high reactivity of the isocyanate group and the amine group to rapidly and in high yield form a urea bond structure under mild conditions, firmly introducing the imidazole functional group into the silane coupling agent molecule. The intermediate has a stable structure and retains the siloxane end groups, facilitating subsequent condensation grafting with hydroxyl groups on the surface of inorganic nanoparticles, thereby ensuring the reproducibility and structural controllability of the functionalized nanoparticle preparation.

[0013] Furthermore, the amine compound containing a complex nitrogen heterocycle is selected from one or more of 1-(3-aminopropyl)imidazolium, 1-(2-aminoethyl)imidazolium, 1-(3-aminopropyl)-2-methylimidazolium, and 4-(2-aminoethyl)pyridine; the isocyanate-containing siloxane is selected from one or more of 3-(triethoxysilyl)propyl isocyanate, 3-isocyanopropyltrimethoxysilane, 3-isocyanopropyltripropoxysilane, and 3-isocyanobutyltriethoxysilane.

[0014] This invention further optimizes the specific types of nitrogen-containing heterocyclic amine compounds and isocyanate siloxanes, all of which possess moderate reactivity and good solubility. In particular, when 1-(3-aminopropyl)imidazolium and 3-(triethoxysilyl)propyl isocyanate are selected, the silane precursor generated by their reaction has a suitable molecular length and flexible propylene spacer chain, which can effectively reduce steric hindrance and allow the imidazolium group to obtain better spatial orientation and accessibility on the nanoparticle surface, thereby enhancing its complexation efficiency with iodine molecules.

[0015] Furthermore, the organic solvent is selected from one or more of tetrahydrofuran, toluene, dimethyl sulfoxide, N,N-dimethylformamide, ethyl acetate, and acetone.

[0016] This invention specifies the types of organic solvents used in the preparation of imidazole silane precursors. These solvents possess good solubility for the reactants and have moderate boiling points, facilitating removal via conventional distillation or washing. In particular, polar aprotic solvents effectively promote the nucleophilic addition reaction between amine groups and isocyanates, increasing the reaction rate and conversion, while avoiding side reactions and ensuring high purity of the precursor.

[0017] Furthermore, the raw materials for preparing the electrolyte include elemental iodine, lithium iodide, 1,2-dimethyl-3-propylimidazolium iodide and 1-methylbenzimidazole (NMBI); the solvents for preparing the electrolyte include ethylene carbonate (EC) and γ-butyrolactone (GBL).

[0018] This invention optimizes the composition of the redox electrolyte by employing a ternary iodine system of I₂ / LiI / ionic liquid (DMPII), which can provide sufficient I₂.- / I3 - The redox pair ensures a high limiting diffusion current density; the addition of NMBI as an additive synergistically suppresses dark current and improves open-circuit voltage. An EC / GBL mixture is selected as the solvent, possessing both high dielectric constant and low viscosity, which facilitates iodide dissociation and rapid ion migration, and exhibits good compatibility with the polyurethane gel precursor, making it easy to form a homogeneous precursor solution.

[0019] This invention also provides a method for preparing an imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte, comprising the following steps: Preparation of liquid electrolyte; A polymer precursor, a crosslinking agent, a catalyst, and imidazole-functionalized inorganic nanoparticles are added to the liquid electrolyte and stirred until homogeneous to obtain a gel electrolyte precursor solution. The gel electrolyte precursor solution was subjected to in-situ polymerization to obtain an imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte.

[0020] The preparation method provided by this invention employs a "one-pot" process, directly dispersing functionalized nanoparticles, polymer precursors, and crosslinking agents in a liquid electrolyte for in-situ polymerization. This process is simple and efficient, avoiding component loss and interfacial defects associated with traditional multi-step solvent exchange or post-impregnation methods. In-situ polymerization allows for the uniform formation of a polyurethane network around the nanoparticles, ensuring a tight interfacial bond and three-dimensional interconnected structure between the organic and inorganic phases, which is beneficial for improving the structural stability and ion conduction uniformity of the electrolyte.

[0021] Furthermore, the amount of imidazole-functionalized inorganic nanoparticles added is 0.1~10 wt% of the total mass of the imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte.

[0022] Further, the mass ratio of the polymer precursor, crosslinking agent, catalyst, and imidazole-functionalized inorganic nanoparticles is 120:20:1:(10~25); the polymer precursor is polyethylene adipate; the crosslinking agent is a mixed solvent of isophorone diisocyanate (IPDI) and hexamethylene diisocyanate trimer (HDI); and the catalyst is dibutyltin dilaurate.

[0023] This invention further optimizes the proportional relationship of key components in the gel electrolyte formulation. Polyethylene adipate (PEG) acts as a soft segment, imparting good flexibility to the gel; the IPDI and HDI trimer composite crosslinking agent can form a network structure with moderate crosslinking density under mild conditions. When the mass ratio of imidazole functionalized nanoparticles to polymer precursor is controlled within the range of (10~25):120, the complexing, anchoring, and toughening effects of the nanoparticles can be fully utilized without increasing gel brittleness or hindering ion transport due to excessive addition, thus achieving the optimal range for overall performance.

[0024] This invention also provides a fiber gel dye-sensitized solar cell, comprising a fiber photoanode, a fiber counter electrode, and an imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte. The fiber photoanode is a titanium dioxide fiber photoanode that adsorbs N719 dye molecules; the fiber counter electrode is a counter electrode formed by winding a carbon nanotube fiber film onto the surface of a titanium wire.

[0025] The gel electrolyte provided by this invention is applied in fiber dye-sensitized solar cells, forming a complete device together with a TiO2 / N719 photoanode and a CNT / titanium wire counter electrode. This cell achieves a photoelectric conversion efficiency of over 7.73% at room temperature, and its performance improves at 100°C (efficiency reaches 7.98%), exhibiting excellent high-temperature stability, flexibility, and photoelectric performance, making it particularly suitable for demanding applications such as wearable devices and outdoor gear.

[0026] This invention also provides a method for preparing a fiber gel dye-sensitized solar cell, comprising the following steps: The fiber photoanode and fiber counter electrode are encapsulated in an encapsulation tube; The imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte is injected into the encapsulation tube and cured to obtain the fiber gel dye-sensitized solar cell.

[0027] This invention provides a method for assembling fiber batteries, in which the photoanode and counter electrode are placed parallel to each other in a transparent encapsulation tube, followed by the injection of a gel electrolyte precursor solution and in-situ curing. This encapsulation method ensures that the gel electrolyte can tightly encapsulate the two fiber electrodes and achieve microscopic wetting, forming a continuous, low-resistance solid-liquid interface contact. The tubular encapsulation structure not only effectively prevents physical leakage of the electrolyte and moisture intrusion, but also endows the device with good bending resistance and shape adaptability, facilitating large-scale continuous production.

[0028] Compared with the prior art, the present invention has the following advantages and technical effects: (1) By introducing imidazole-functionalized alumina nanoparticles, the present invention utilizes the complexation between the imidazole group and the iodine group to effectively inhibit the erosion of dyes by iodine under high temperature conditions and improve the high temperature stability of the device.

[0029] (2) The organic-inorganic hybrid gel network constructed in this invention can reduce the local crystallinity of the polymer and improve the continuity of ion migration channels, thereby improving the ion conductivity of the gel electrolyte and the efficiency of interfacial charge transport.

[0030] (3) In this invention, functionalized alumina nanoparticles serve as structural nodes in the gel network, which can improve the mechanical strength and flexibility of the gel system, enabling the device to maintain high performance after multiple bending and twisting.

[0031] (4) The fiber gel dye-sensitized solar cell prepared by the present invention can still work stably at 100°C and retain more than 90% of its initial performance after 1000 bending cycles. Attached Figure Description

[0032] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 Transmission electron microscopy (a) and XRD results (b) of the imidazole-functionalized alumina nanoparticles prepared in Example 1. Figure 2 The image shows the actual gel electrolyte prepared in Example 1. Figure 3 This is a schematic diagram of the overall structure of the fiber dye-sensitized solar cell of the present invention; wherein, 1-counter electrode; 2-gel electrolyte; 3-fiber photoanode; 4-inorganic nanoparticles; 2.1-free iodine molecule; 2.2-gel framework; Figure 4 This is a flowchart illustrating the fabrication process of the fiber dye-sensitized solar cell of the present invention. Figure 5 The images are scanning electron microscope (SEM) images of the fiber photoanode and the fiber counter electrode; where a is the oxidized fiber photoanode; b is a magnified image of titanium dioxide nanotubes on the fiber photoanode; c is the fiber counter electrode coated with a carbon nanotube film; and d is a magnified image of carbon nanotube fibers on the fiber counter electrode. Figure 6 The graph shows the photovoltaic performance of the fiber dye-sensitized solar cell prepared using Example 1; where a is the current density-voltage ratio at room temperature. JV (Curve); b is the current density-voltage ratio at 100℃. JV curve); Figure 7 The graph shows the bending stability test results of the fiber dye-sensitized solar cell prepared in Example 1. Figure 8 The graph shows the photovoltaic performance of the fiber dye-sensitized solar cell prepared in Example 2; where a is the current density-voltage ratio at room temperature. JV (Curve); b is the current density-voltage ratio at 100℃. JV curve); Figure 9 The graph shows the photovoltaic performance of the fiber dye-sensitized solar cell prepared in Example 3; where a is the current density-voltage ratio at room temperature. JV (Curve); b is the current density-voltage ratio at 100℃. JV curve); Figure 10The photovoltaic performance test graph of the fiber dye-sensitized solar cell prepared in Example 1 is shown for comparison; where a is the current density-voltage ratio at room temperature. JV (Curve); b is the current density-voltage ratio at 100℃. JV curve); Figure 11 The photovoltaic performance test graph of the fiber dye-sensitized solar cell prepared in Example 2 is shown for comparison; where a is the current density-voltage ratio at room temperature. JV (Curve); b is the current density-voltage ratio at 100℃. JV curve); Figure 12 The photovoltaic performance test graph of the fiber dye-sensitized solar cell prepared in Example 3 is shown for comparison; where a is the current density-voltage ratio at room temperature. JV (Curve); b is the current density-voltage ratio at 100℃. JV curve). Detailed Implementation

[0033] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0034] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0035] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0036] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0037] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0038] The electrolyte provided by this invention is created by functionalizing inorganic nanoparticles with imidazole groups and introducing them into a polyurethane gel electrolyte system to construct an organic-inorganic hybrid gel network. The imidazole groups can form complexes with free iodine molecules in the electrolyte, inhibiting the erosion of N719 dye molecules by iodine under high-temperature conditions and improving the high-temperature stability of the device. This gel electrolyte is used in fiber dye-sensitized solar cells. The process involves placing a titanium dioxide fiber photoanode and a fiber counter electrode (both adsorbed with N719 dye molecules) in a flexible transparent tube, injecting a gel electrolyte precursor solution into the tube for in-situ polymerization, allowing the electrolyte to tightly coat and microscopically wet the two fiber electrodes, and sealing with hot melt adhesive to obtain the fiber gel dye-sensitized solar cell. The fiber gel dye-sensitized solar cell prepared by this invention exhibits significantly improved high-temperature stability, excellent flexibility, and good photoelectric conversion performance, making it suitable for flexible photovoltaic device applications.

[0039] The imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte provided by this invention uses polyurethane polymer as the polymer gel backbone, an electrolyte containing an iodine redox couple as the ion transport medium, and introduces polyurethane polymer containing imidazole-functionalized inorganic nanoparticles to form an organic-inorganic hybrid gel network; wherein: the imidazole-functionalized inorganic nanoparticles are obtained by reacting inorganic nanoparticles with hydroxyl groups on the surface with imidazole-containing silane precursors, and can form complexes with free iodine in the electrolyte; the polyurethane polymer is formed by in-situ crosslinking of monomers containing isocyanate groups and monomers containing hydroxyl groups.

[0040] This invention provides an imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte, which is formed by using a polyurethane polymer containing imidazole-functionalized inorganic nanoparticles to form an organic-inorganic hybrid gel network and accommodating an electrolyte containing an iodine redox couple to form a hybrid gel electrolyte; the imidazole-functionalized inorganic nanoparticles are obtained by reacting inorganic nanoparticles with an imidazole-containing silane precursor; the polyurethane polymer is formed by in-situ polymerization of monomers containing isocyanate groups and monomers containing hydroxyl groups.

[0041] In the following optional embodiments of the present invention, the inorganic nanoparticles are metal oxide nanoparticles with hydroxyl groups on their surface, selected from one or more of aluminum oxide (Al2O3), silicon dioxide (SiO2), titanium dioxide (TiO2), zinc oxide (ZnO), zirconium oxide (ZrO2), and iron oxide (Fe2O3 or Fe3O4); the average particle size of the inorganic nanoparticles is 5-200 nm. Exemplarily, in the following preferred embodiments of the present invention, the inorganic nanoparticles may be aluminum oxide or silicon dioxide.

[0042] In the following optional embodiments of the present invention, during the preparation of imidazole-functionalized inorganic nanoparticles, the imidazole-containing silane precursor is obtained by reacting an amine compound containing a complexed nitrogen heterocycle with an isocyanate-containing siloxane in an organic solvent. The amine compound containing the complexed nitrogen heterocycle is selected from one or more of 1-(3-aminopropyl)imidazolium, 1-(2-aminoethyl)imidazolium, 1-(3-aminopropyl)-2-methylimidazolium, and 4-(2-aminoethyl)pyridine; exemplaryly, in the following preferred embodiments of the present invention, the amine compound containing the complexed nitrogen heterocycle is selected from 1-(3-aminopropyl)imidazolium. The isocyanate-containing siloxane is selected from one or more of 3-(triethoxysilyl)propyl isocyanate, 3-isocyanopropyltrimethoxysilane, 3-isocyanopropyltripropoxysilane, and 3-isocyanobutyltriethoxysilane; exemplaryly, in the following preferred embodiments of the present invention, the isocyanate-containing siloxane is selected from 3-(triethoxysilyl)propyl isocyanate. The organic solvent is selected from one or more of tetrahydrofuran, toluene, dimethyl sulfoxide, N,N-dimethylformamide, ethyl acetate, and acetone. Exemplarily, in the following preferred embodiments of the present invention, the organic solvent is selected from dimethyl sulfoxide.

[0043] An exemplary method for preparing imidazole-functionalized inorganic nanoparticles includes the following steps: dissolving an amine compound containing a complexed nitrogen heterocycle in an organic solvent, adding an isocyanate-containing siloxane, and heating the mixture under nitrogen protection (reacting at 80°C for 8 hours) to obtain a silane precursor containing an imidazole group; dispersing inorganic nanoparticles in an organic solvent, ultrasonically homogenizing them, adding the above silane precursor, and continuing the heating reaction (reacting at 80°C for 24 hours); after the reaction is completed, washing with ethanol, centrifuging, and drying to obtain imidazole-functionalized inorganic nanoparticles.

[0044] In the following optional embodiments of the present invention, the raw materials for preparing the electrolyte include elemental iodine, lithium iodide, 1,2-dimethyl-3-propylimidazolium iodide, and 1-methylbenzimidazole; the solvent for preparing the electrolyte includes ethylene carbonate and γ-butyrolactone. Exemplarily, in the following preferred embodiments of the present invention, the molar concentration (mM) ratio of elemental iodine, lithium iodide, 1,2-dimethyl-3-propylimidazolium iodide, and 1-methylbenzimidazole is 6:100:600:500, and the volume ratio of ethylene carbonate to γ-butyrolactone is 3:7.

[0045] For example, the preparation method of the electrolyte includes the following steps: dissolving raw materials (iodine, lithium iodide, 1,2-dimethyl-3-propylimidazolium iodide and 1-methylbenzimidazole) in a solvent (a mixture of ethylene carbonate and γ-butyrolactone) to obtain the electrolyte.

[0046] This invention also provides a method for preparing an imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte, comprising the following steps: Prepare a liquid electrolyte; add a polymer precursor, crosslinking agent, catalyst and imidazole-functionalized inorganic nanoparticles to the liquid electrolyte, stir evenly to obtain a gel electrolyte precursor solution; carry out an in-situ polymerization reaction on the gel electrolyte precursor solution to obtain an imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte.

[0047] In the following optional embodiments of the present invention, the amount of imidazole-functionalized inorganic nanoparticles added is 0.1 to 10 wt% (e.g., 1.0 wt% or 2.5 wt%) of the total mass of the imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte.

[0048] In the following optional embodiments of the present invention, the polymer precursor is polyethylene adipate; the crosslinking agent is a mixed solvent of isophorone diisocyanate and hexamethylene diisocyanate trimer (mass ratio of the two is 3:17); and the catalyst is dibutyltin dilaurate.

[0049] In the following optional embodiments of the present invention, the mass ratio of polymer precursor, crosslinking agent, catalyst and imidazole functionalized inorganic nanoparticles is 120:20:1:(10~25), such as 120:20:1:10 or 120:20:1:25.

[0050] In the following optional embodiments of the present invention, the in-situ polymerization reaction is to stir the gel electrolyte precursor solution (stirring at 200 r / min for 1 h) and then heat it for reaction (reacting at 60°C for 3 h).

[0051] The imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte provided by this invention can be used to prepare fiber gel dye-sensitized solar cells. The cell includes a fiber photoanode, a fiber counter electrode, and the imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte. Specifically, the fiber photoanode is a titanium dioxide fiber photoanode that adsorbs N719 dye molecules; the fiber counter electrode is a counter electrode formed by winding a carbon nanotube fiber film onto the surface of a titanium wire.

[0052] The method for preparing the fiber gel dye-sensitized solar cell includes the following steps: encapsulating the fiber photoanode and fiber counter electrode in an encapsulation tube; injecting imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte into the encapsulation tube and performing a curing treatment to obtain the fiber gel dye-sensitized solar cell.

[0053] An exemplary method for preparing a fiber-gel dye-sensitized solar cell includes the following steps: cleaning titanium wire, preparing a TiO2 nanotube array on the surface of titanium wire using anodizing, annealing treatment (annealing at 510℃ for 1 h), and immersing the resulting product in an N719 dye solution; winding a carbon nanotube fiber film onto the surface of titanium wire using a wrapping process, with the following process parameters: winding speed 1 m / min, winding pitch 60 μm, and film thickness approximately 20 μm; placing the fiber photoanode and fiber counter electrode parallel to each other in a transparent encapsulation tube, with both ends extending outside the tube, injecting a gel electrolyte, sealing the tube opening with hot melt adhesive, and heating and curing (heating at 60℃ for 3 h) to obtain a fiber-gel dye-sensitized solar cell.

[0054] An exemplary method for preparing imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte and fiber gel dye-sensitized solar cells includes the following steps: I. Preparation of Imidazole-functionalized Inorganic Nanoparticles Step (1) Synthesis of imidazole-containing silane precursor: 1-(3-aminopropyl)imidazolium was dissolved in dimethyl sulfoxide (DMSO), and 3-(triethoxysilyl)propyl isocyanate was added. The reaction was carried out at 80°C for 8 hours under nitrogen protection to obtain silane precursor containing imidazole group. Step (2) Nanoparticle functionalization modification: Inorganic nanoparticles (Al2O3 or SiO2) were dispersed in DMSO, ultrasonically homogenized, and then the above-mentioned silane precursor was added. The reaction was carried out at 80°C for 24 h. After the reaction was completed, the nanoparticles were washed with ethanol, centrifuged, and dried to obtain imidazole-functionalized inorganic nanoparticles. II. Preparation of Gel Electrolytes Step (1) Preparation of liquid electrolyte: Dissolve elemental iodine (6mM), lithium iodide (0.1M), 1,2-dimethyl-3-propylimidazolium iodide (0.6M), and 1-methylbenzimidazole (0.5M) in a mixed solvent of ethylene carbonate / γ-butyrolactone (volume ratio 3:7); Step (2) Preparation of precursor solution: Add the following components to the obtained liquid electrolyte (wt% in the following components represents the mass percentage of the corresponding substance added to the liquid electrolyte): Polymer precursor: 12wt% polyethylene adipate; Crosslinking agent: 0.3wt% isophorone diisocyanate + 1.7wt% hexamethylene diisocyanate trimer; Catalyst: 0.1wt% dibutyltin dilaurate; Functionalized nanoparticles: 2.5 wt% or 1 wt%; The mixture was stirred at 200 r / min for 1 h, followed by heating at 60 °C for 3 h to obtain a gel electrolyte. III. Assembly of Fiber Dye-Sensitized Solar Cells Step (1) Preparation of fiber photoanodes: clean titanium wire (acetone → isopropanol → deionized water, each ultrasonic for 10 min), prepare TiO2 nanotube array on the surface of titanium wire by anodic oxidation, anneal at 510℃ for 1 h, and soak the obtained product in N719 dye solution for 48 h. Step (2) Preparation of fiber counter electrode: Carbon nanotube fiber film is wound onto the surface of titanium wire by a winding process. Process parameters: winding speed 1m / min, winding pitch 60μm, film thickness about 20μm; Step (3) Assemble the battery: Place the photoanode and the counter electrode parallel in a transparent encapsulation tube with both ends extending out of the tube, inject gel electrolyte, seal the tube opening with hot melt adhesive, and heat at 60°C for 3 hours to obtain a fiber gel dye-sensitized solar cell.

[0055] Unless otherwise specified, "room temperature" in this invention refers to 25±2℃.

[0056] All reagents used in the following examples were purchased externally, including various solvents, dyes, and electrolyte solutions, all of which were purchased from Sinopharm Chemical Reagent Co., Ltd. All equipment used in the following examples was commercially available.

[0057] The technical solution of the present invention will be further illustrated by the following embodiments.

[0058] Example 1 The preparation steps of an imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte are as follows: (I) Preparation of imidazole-functionalized alumina nanoparticles: Step (1): Dissolve 2g of 1-(3-aminopropyl)imidazolium in 25mL of dimethyl sulfoxide, then add 3.09g of 3-(triethoxysilyl)propyl isocyanate, and react at 80℃ for 8h under nitrogen protection to obtain a silane precursor containing an imidazolium group; Step (2): 0.5g of alumina nanoparticles were dispersed in 50mL of dimethyl sulfoxide and uniformly dispersed by ultrasonic treatment. The above-mentioned silane precursor was added to it and reacted at 80℃ for 24h. After the reaction was completed, the nanoparticles were washed with ethanol, centrifuged, and completely dried in an oven to finally obtain imidazole functionalized alumina nanoparticles. (II) Preparation of gel electrolytes: Step (1): Dissolve 6 mM iodine, 0.1 M lithium iodide, 0.6 M 1,2-dimethyl-3-propylimidazolium iodide and 0.5 M 1-methylbenzimidazole in a mixed solvent of ethylene carbonate / γ-butyrolactone (volume ratio 3:7) to obtain a liquid electrolyte. Step (2): Add 12wt% polyethylene adipate, 0.3wt% isophorone diisocyanate, 1.7wt% hexamethylene diisocyanate trimer, 0.1wt% dibutyltin dilaurate and 2.5wt% imidazole functionalized alumina nanoparticles to the obtained liquid electrolyte, stir uniformly at 200 r / min for 1 h, and then heat at 60℃ for 3 h to prepare gel electrolyte.

[0059] Figure 1 Transmission electron microscopy (TEM) image (a) and XRD results (b) of the imidazole-functionalized alumina nanoparticles prepared in Example 1; from Figure 1 As can be seen from 'a', the alumina nanoparticles modified with imidazole silane exhibit a near-spherical morphology with a particle size of approximately 20–30 nm. There are no obvious hard agglomerations between the particles, and the dispersion is good. Figure 1 In the XRD diffraction pattern of b, the positions of each characteristic peak are in good agreement with the γ-Al2O3 standard card (JCPDS No. 10-0425), and no other impurity peaks appear, indicating that the imidazole functionalization surface modification process did not change the bulk crystal structure of the alumina nanoparticles.

[0060] Figure 2 The image shows the gel electrolyte prepared in Example 1. As can be seen from the image, the prepared gel electrolyte is a uniform, semi-transparent gel. After the sample bottle is inverted, there is no macroscopic flow phenomenon in the gel, indicating that the polyurethane polymer precursor has been successfully cross-linked to form a stable three-dimensional network framework, and the imidazole functionalized nanoparticles are uniformly dispersed in the system without sedimentation or phase separation.

[0061] Application Example 1 Fabrication of fiber dye-sensitized solar cells (flowchart shown) Figure 4 The steps are as follows: Step (1): The titanium wire with a diameter of 0.15 mm was ultrasonically cleaned with acetone, isopropanol and deionized water for 10 min each time. After drying, a vertically oriented titanium dioxide nanotube array was prepared on the surface of the titanium wire by anodizing. Then, it was annealed at 510 °C for 1 h in air atmosphere and immersed in N719 dye solution for 48 h to obtain fiber photoanode. Step (2): Select a carbon nanotube fiber film and wrap it evenly on the surface of a titanium wire with a diameter of 0.15 mm through a wrapping process of unwinding, guiding, winding and rewinding; wherein the winding speed is 1 m / min and the winding pitch is 60 μm, thereby forming a dense carbon nanotube fiber film with a thickness of about 20 μm on the surface of the titanium wire, and obtaining the fiber counter electrode. Step (3): Place the fiber photoanode and fiber counter electrode together in a transparent encapsulation tube, with both ends of the electrodes extending out of the encapsulation tube; then inject the gel electrolyte prepared in Example 1 into the encapsulation tube, and seal the tube opening with hot melt adhesive; finally, heat and cure at 60°C for 3 hours to obtain a fiber dye-sensitized solar cell (see schematic diagram of the overall structure). Figure 3 , where 1-pair of electrodes; 2-gel electrolyte; 3-fiber photoanode; 4-inorganic nanoparticles; 2.1-free iodine molecules; 2.2-gel framework).

[0062] Figure 5 The images are scanning electron microscope (SEM) images of the fiber photoanode and the fiber counter electrode, where (a) is the oxidized fiber photoanode; (b) is a magnified image of titanium dioxide nanotubes on the fiber photoanode; (c) is the fiber counter electrode coated with a carbon nanotube film; and (d) is a magnified image of carbon nanotube fibers on the fiber counter electrode. Figure 5 In Figure 'a', the surface of the titanium wire after anodizing and annealing is covered with a uniform porous oxide layer. Figure 5 The high-magnification scanning electron microscope image of b clearly shows a vertically oriented and regularly arranged array of titanium dioxide nanotubes. The inner diameter of the nanotubes is about 80-100 nm, indicating that the structure has a large specific surface area, which is beneficial to the efficient adsorption of N719 dye. Figure 5 The image shows that the carbon nanotube fiber film is uniformly and tightly bonded to the surface of the titanium wire through a wrapping process, with complete coverage and no exposed areas. Figure 5 The high-magnification image of d further reveals that the carbon nanotubes are intertwined and entangled, forming a continuous three-dimensional conductive network, which is beneficial for the catalytic reaction of the electrode and charge collection.

[0063] Figure 6 In Figure 'a', the current density-voltage relationship curve of the fiber dye-sensitized solar cell prepared in Example 1 is measured under standard AM 1.5 sunlight. Its open-circuit voltage is 0.78V and its short-circuit current density is 15.3mA / cm². 2 With a fill factor of 0.65 and an energy conversion efficiency of 7.73%, the device exhibits excellent performance. b shows the current density-voltage relationship curve of the device under standard sunlight at 100℃, with an open-circuit voltage of 0.73V and a short-circuit current density of 15.4mA / cm². 2 With a fill factor of 0.71 and an energy conversion efficiency of 7.98%, it exhibits excellent thermal stability.

[0064] Figure 7 The figure shows the bending performance test results of the fiber dye-sensitized solar cell prepared in Application Example 1. When the bending diameter is 1 cm and the number of bends is 1000, the photoelectric conversion efficiency retention rate exceeds 90%.

[0065] Example 2 Same as Example 1, except that in step (ii) of preparing the gel electrolyte, the amount of imidazole-functionalized alumina nanoparticles added is adjusted to 1 wt%.

[0066] Application Example 2 Similar to Application Example 1, except that the gel electrolyte prepared in Example 1 is replaced by the gel electrolyte prepared in Example 2 in equal mass.

[0067] Figure 8 In Figure 'a', the current density-voltage relationship curve of the fiber dye-sensitized solar cell prepared in Example 2 is measured under standard AM 1.5 sunlight. Its open-circuit voltage is 0.77V and its short-circuit current density is 11.9mA / cm². 2 With a fill factor of 0.66 and a power conversion efficiency of 6.06%, the device exhibits excellent performance. b shows the current density-voltage relationship curve of the device under standard sunlight at 100℃, with an open-circuit voltage of 0.73V and a short-circuit current density of 14.2mA / cm². 2 With a fill factor of 0.70 and an energy conversion efficiency of 7.24%, it exhibits excellent thermal stability.

[0068] Example 3 Same as Example 1, except that in step (a) of preparing imidazole functionalized alumina nanoparticles, alumina nanoparticles are replaced with silica nanoparticles by the same mass.

[0069] Application Example 3 Similar to Application Example 1, except that the gel electrolyte prepared in Example 1 is replaced by the gel electrolyte prepared in Example 3 in equal mass.

[0070] Figure 9 In Figure 'a', the current density-voltage curve of the fiber dye-sensitized solar cell prepared in Example 3 is measured under standard AM 1.5 sunlight. Its open-circuit voltage is 0.77V and its short-circuit current density is 14.5mA / cm². 2 With a fill factor of 0.64 and an energy conversion efficiency of 7.17%, the device exhibits excellent performance. b shows the current density-voltage relationship curve of the device under standard sunlight at 100℃, with an open-circuit voltage of 0.75V and a short-circuit current density of 14.3mA / cm². 2 With a fill factor of 0.68 and an energy conversion efficiency of 7.38%, it exhibits excellent thermal stability.

[0071] Comparative Example 1 Same as Example 1, except that in the preparation of gel electrolyte in step (II), "2.5wt% imidazole functionalized alumina nanoparticles" are replaced with "2.5wt% unmodified raw alumina nanoparticles".

[0072] Comparative Application Example 1 Similar to Application Example 1, except that the gel electrolyte prepared in Example 1 is replaced by the gel electrolyte prepared in Comparative Example 1 in equal mass.

[0073] Test results: Figure 10 In Figure 'a', the current density-voltage relationship curve of the fiber dye-sensitized solar cell prepared in Comparative Example 1 is measured under standard AM 1.5 sunlight. Its open-circuit voltage is 0.77V and its short-circuit current density is 14.6mA / cm². 2 With a fill factor of 0.60 and a power conversion efficiency of 7.03%, the device exhibits excellent performance. b shows the current density-voltage relationship curve of the device under standard sunlight at 100℃, with an open-circuit voltage of 0.73V and a short-circuit current density of 12.6mA / cm². 2 The fill factor is 0.69 and the energy conversion efficiency is 6.34%.

[0074] Comparative Example 2 Same as Example 1, except that in the preparation of the gel electrolyte in step (II), the mass of "2.5wt% imidazole functionalized alumina nanoparticles" is replaced with "2.5wt% 1-(3-aminopropyl)imidazolium free small molecules".

[0075] Comparative Application Example 2 Similar to Application Example 1, except that the gel electrolyte prepared in Example 1 is replaced by the gel electrolyte prepared in Comparative Example 2 in equal mass.

[0076] Test results: Figure 11 In Figure 'a', the current density-voltage relationship curve of the fiber dye-sensitized solar cell prepared in Comparative Example 2 under standard AM 1.5 sunlight is shown. Its open-circuit voltage is 0.77V and its short-circuit current density is 14.2mA / cm². 2 With a fill factor of 0.60 and a power conversion efficiency of 7.04%, the device exhibits excellent performance. b shows the current density-voltage relationship curve of the device under standard sunlight at 100℃, with an open-circuit voltage of 0.74V and a short-circuit current density of 14.5mA / cm². 2 With a fill factor of 0.68 and an energy conversion efficiency of 7.28%, it exhibits excellent thermal stability.

[0077] Comparative Example 3 Same as Example 1, except that in step (ii) of preparing the gel electrolyte, the amount of imidazole-functionalized alumina nanoparticles added is adjusted to 5.0 wt%.

[0078] Comparative Application Example 3 Similar to Application Example 1, except that the gel electrolyte prepared in Example 1 is replaced by the gel electrolyte prepared in Comparative Example 3 in equal mass.

[0079] Test results: Figure 12 In Figure 'a', the current density-voltage relationship curve of the fiber dye-sensitized solar cell prepared in Comparative Example 3 under standard AM 1.5 sunlight is shown. Its open-circuit voltage is 0.77V and its short-circuit current density is 12.5mA / cm². 2 With a fill factor of 0.62 and an energy conversion efficiency of 6.43%, the device exhibits excellent performance. b shows the current density-voltage relationship curve of the device under standard sunlight at 100℃, with an open-circuit voltage of 0.74V and a short-circuit current density of 13.2mA / cm². 2 With a fill factor of 0.71 and an energy conversion efficiency of 6.92%, it exhibits excellent thermal stability.

[0080] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. An imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte, characterized in that, An organic-inorganic hybrid gel network is formed by using a polyurethane polymer containing imidazole-functionalized inorganic nanoparticles, and an electrolyte containing an iodine redox couple is contained to form a hybrid gel electrolyte. The imidazole-functionalized inorganic nanoparticles are obtained by reacting inorganic nanoparticles with an imidazole-containing silane precursor. The polyurethane polymer is formed by in-situ polymerization of monomers containing isocyanate groups and monomers containing hydroxyl groups.

2. The imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte according to claim 1, characterized in that, The inorganic nanoparticles are metal oxide nanoparticles with hydroxyl groups on their surface, selected from one or more of aluminum oxide, silicon dioxide, titanium dioxide, zinc oxide, zirconium oxide and iron oxide; the average particle size of the inorganic nanoparticles is 5 to 200 nm.

3. The imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte according to claim 1, characterized in that, In the preparation of the imidazole-functionalized inorganic nanoparticles, the imidazole-containing silane precursor is obtained by reacting an amine compound containing a complex nitrogen heterocycle with an isocyanate-containing siloxane in an organic solvent.

4. The imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte according to claim 3, characterized in that, The amine compound containing a complex nitrogen heterocycle is selected from one or more of 1-(3-aminopropyl)imidazolium, 1-(2-aminoethyl)imidazolium, 1-(3-aminopropyl)-2-methylimidazolium, and 4-(2-aminoethyl)pyridine; The isocyanate-containing siloxane is selected from one or more of 3-(triethoxysilyl)propyl isocyanate, 3-isocyanate-propyltrimethoxysilane, 3-isocyanate-propyltripropoxysilane, and 3-isocyanate-butyltriethoxysilane.

5. The imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte according to claim 3, characterized in that, The organic solvent is selected from one or more of tetrahydrofuran, toluene, dimethyl sulfoxide, N,N-dimethylformamide, ethyl acetate, and acetone.

6. The imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte according to claim 1, characterized in that, The raw materials for preparing the electrolyte include elemental iodine, lithium iodide, 1,2-dimethyl-3-propylimidazolium iodide, and 1-methylbenzimidazole; the solvents for preparing the electrolyte include ethylene carbonate and γ-butyrolactone.

7. A method for preparing an imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte as described in any one of claims 1 to 6, characterized in that, Includes the following steps: Preparation of liquid electrolyte; A polymer precursor, a crosslinking agent, a catalyst, and imidazole-functionalized inorganic nanoparticles are added to the liquid electrolyte and stirred until homogeneous to obtain a gel electrolyte precursor solution. The gel electrolyte precursor solution was subjected to in-situ polymerization to obtain an imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte.

8. The preparation method according to claim 7, characterized in that, The mass ratio of the polymer precursor, crosslinking agent, catalyst, and imidazole-functionalized inorganic nanoparticles is 120:20:1:(10~25); the polymer precursor is polyethylene adipate; the crosslinking agent is a mixed crosslinking agent of isophorone diisocyanate and hexamethylene diisocyanate trimer; and the catalyst is dibutyltin dilaurate.

9. A fiber gel dye-sensitized solar cell, characterized in that, The invention includes a fiber photoanode, a fiber counter electrode, and an imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte as described in any one of claims 1 to 6; wherein the fiber photoanode is a titanium dioxide fiber photoanode that adsorbs N719 dye molecules; and the fiber counter electrode is a counter electrode formed by winding a carbon nanotube fiber film around the surface of a titanium wire.

10. A method for preparing a fiber gel dye-sensitized solar cell as described in claim 9, characterized in that, Includes the following steps: The fiber photoanode and fiber counter electrode are encapsulated in an encapsulation tube; The imidazole-functionalized inorganic nanoparticle hybrid gel electrolyte is injected into the encapsulation tube and cured to obtain the fiber gel dye-sensitized solar cell.